Serum Levels of Soluble Urokinase Plasminogen Activator Receptor in Infants with Late‐onset Sepsis. Issue 5 (10th July 2014) - Okulu, Emel; Arsan, Saadet; Akin, Ilke Mungan; Ates, Can; Alan, Serdar; Kilic, Atila; Atasay, Begum
<x xml:space="preserve">Abstract</x> Background Soluble urokinase plasminogen activator receptor (suPAR) has been studied in a variety of diseases. The aim of the study is to investigate the levels of suPAR in neonates with sepsis. Methods The infants enrolled to this prospective study were classified into four groups. Group 1, 2, and 3 were referred as the patient groups (40 infants), and group 4 was referred as control group (26 infants). Blood samples for whole blood count, C‐reactive protein (CRP), suPAR and blood culture were obtained before initiating antimicrobial therapy, and two further samples were obtained on day 3 and at the end of the treatment for CRP and suPAR. Results The mean gestational ages of patient and control groups was similar. The median level of initial suPAR was 18.8 ng/mL (range 6.8–30.1 ng/mL) in the patient groups, and 6.0 ng/mL (range 3.7–10.8 ng/mL) in the control group (P < 0.001). A significant decrease in suPAR level was observed from the inclusion to the third day and end of the treatment (P < 0.001). The area under the curve (AUC) for suPAR is 0.959 (95% Cl: 0.919–0.999) and for CRP is 0.782 (95% Cl: 0.669–0.895). At a cut‐off value of 11.3 ng/mL for suPAR the specificity was 100%, and the sensitivity was 82.5%. There was a positive correlation between laboratory values of CRP and suPAR (r: 0.359, P = 0.003). Conclusion This is the first study that investigated the levels of suPAR in neonates and our results demonstrate that suPAR is a powerful marker of inflammation in infants with sepsis.